PMMA-collagen Gel in Nonsurgical Rhinoplasty Defects: A Methodological Overview and 15-year Experience. Issue 8 (19th August 2022) - Rivkin, Alexander
Abstract : Background: Nonsurgical rhinoplasty (NSR) is an alternative to surgical rhinoplasty for patients who desire correction of mild-to-moderate aesthetic nasal defects but do not wish to undergo surgery due to concern about risks, recovery time, or cost. Although not a surrogate, NSR can be a more accessible and more precise modality for achieving aesthetic goals. Furthermore, for certain types of defects, the precision possible with filler injection versus surgery can make NSR the preferred procedure. In these instances, polymethylmethacrylate (PMMA)-collagen gel is a valuable tool for appropriate candidates due to its permanence and its favorable safety profile when injected appropriately. Methods: Optimal use of PMMA-collagen gel for NSR is predicated on expert-level injector experience and careful patient selection and education. The author draws on over 15 years of experience treating more than 1000 NSR patients with PMMA-collagen gel to provide a discussion of relevant anatomy; methodological overview, including patient selection; and a video describing injection technique of NSR with PMMA-collagen gel. Results: To our knowledge, this is the first published guidance on NSR with permanent filler. In addition to the clinical experience provided, patient images with 10 years of follow-up are included to illustrate the durability of the results and the continued natural appearance of the correction as the treated patients continue to age. Conclusion: In patients with aesthetic nasal deficits treated with filler, where permanent correction is desired, the appropriate use of PMMA-collagen gel is an effective treatment option.